1999
DOI: 10.1148/radiology.210.1.r99ja0371
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Importance of Small Hepatic Lesions Found at CT in Patients with Cancer

Abstract: Although small hepatic lesions in patients with cancer more frequently are benign than malignant, these lesions represent metastases in 11.6% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
0
12

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(130 citation statements)
references
References 7 publications
7
111
0
12
Order By: Relevance
“…Among those, the majority correspond to cysts, haemangiomas, focal nodular hyperplasia, adenomas and pseudolesions, such as focal fatty infiltration and focal fatty sparing [2]. It has been demonstrated that the majority of incidental focal liver lesions discovered during any abdominal imaging work-up is, in fact, benign and devoided of particular clinical significance, even in oncologic patients [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among those, the majority correspond to cysts, haemangiomas, focal nodular hyperplasia, adenomas and pseudolesions, such as focal fatty infiltration and focal fatty sparing [2]. It has been demonstrated that the majority of incidental focal liver lesions discovered during any abdominal imaging work-up is, in fact, benign and devoided of particular clinical significance, even in oncologic patients [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…12 In our study, only 68% of patients had benign lesions, primarily because of the exclusion criteria exercised in respect of simple cysts detected on USG/CT. While the most common malignant liver lesions are metastases, the common primary hepato-biliary malignant lesions are hepato-cellular carcinoma (HCC) and intra-hepatic cholangio-carcinoma.…”
Section: Discussionmentioning
confidence: 72%
“…A high level of observer uncertainty may account for the poor interobserver agreement for the 4.8-mm lesion under framed conditions: While the large opacity was clearly noticeable and the small opacity definitely invisible at most settings, the conspicuousness of the intermediate lesion was more ambiguous and some observers may have overestimated their confidence in perceiving this lesion because its location could be accurately determined by adjacent opacities that were plainly visible due to their larger size and/or greater density difference to the background. Hepatic lesions smaller than 10 mm in diameter are likely to be benign, particularly in patients with no history of malignancy [13,14,20]. Our results suggest that the use of a phantom with fixed lesion location may therefore be adequate for optimization of routine liver protocols when the detection of small lesions is not required.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, to our knowledge, the requirement for randomization of disease presence and/or location for CT dose optimization purposes has not been established. In the clinical setting, the diagnostic task of lesion detection usually involves visual search [18,19] and a predominance of normal cases [13,20], elements that are absent in a typical CT optimization methodology involving a phantom with fixed location of lesions. It has been shown that if an observer receives visual cues for the location or presence of an abnormality, sensitivity is increased [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation